EMPOWERING WOMEN ENTREPRENEURS: ENHANCING COMPETENCY AND CAPACITY THROUGH UNIVERSITY EDUCATION - Putri Khalijah Tricahyanti Siregar; Ritha F. Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
This research aims to explore the potential of human capital, competitive advantages, and women entrepreneurship innovation in Indonesia and Kuala Lumpur, as well as to provide academic policies to the government by establishing a cluster of human resources (HR) expertise and enhancing the development of women entrepreneurship, resulting in regulations to improve human capital and women entrepreneurship. The research problem is how female entrepreneurs can transform HR expertise in their business. The survey sample of active female entrepreneurs in various cities were selected using a multi-stage random sampling method, totaling 47 female entrepreneurs, consisting of 39 respondents from Medan and Deli Serdang, 5 from West Sumatra, and 3 from Kelantan, Malaysia. The qualitative descriptive research and a comparative analysis were applied to this research. This research proves that female entrepreneurs who act as housewives must continue to develop their human resource potential, competitive advantages, and innovative abilities in entrepreneurship to produce superior products, be competitive, increase economic income, and improve the welfare of their families.